Mitf Involved in Innate Immunity by Activating Tyrosinase-Mediated Melanin Synthesis in Pteria penguin - Yu, Feifei; Lu, Yishan; Zhong, Zhiming; Qu, Bingliang; Wang, Meifang; Yu, Xiangyong; Chen, Jiayu (Frontiers in Immunology, 2021)
The microphthalmia-associated transcription factor (MITF) is an important transcription factor that plays a key role in melanogenesis, cell proliferation, survival and immune defense in vertebrate. However, its function and function mechanism in bivalve are still rarely known. In this research, first, a Mitf gene was characterized from Pteria penguin (P. penguin). The PpMitf contained an open reading frame of 1350 bp, encoding a peptide of 449 deduced amino acids with a highly conserved basic helix-loop-helix-leucine zipper (bHLH-LZ) domain. The PpMITF shared 55.7% identity with amino acid sequence of Crassostrea gigas (C. gigas). Tissue distribution analysis revealed that PpMitf was highly expressed in mantle and heamocytes, which were important tissues for color formation and innate immunity. Second, the functions of PpMitf in melanin synthesis and innate immunity were identified. The PpMitf silencing significantly decreased the tyrosinase activity and melanin content, indicating PpMitf involved in melanin synthesis of P. penguin. Meanwhile, the PpMitf silencing clearly down-regulated the expression of PpBcl2 (B cell lymphoma/leukemia-2 gene) and antibacterial activity of hemolymph supernatant, indicating that PpMitf involved in innate immunity of P. penguin. Third, the function mechanism of PpMitf in immunity was analyzed. The promoter sequence analysis of tyrosinase (Tyr) revealed two highly conserved E-box elements, which were specifically recognized by HLH-LZ of MITF. The luciferase activities analysis showed that Mitf could activate the E-box in Tyr promoter through highly conserved bHLH-LZ domain, and demonstrated that PpMitf involved in melanin synthesis and innate immunity by regulating tyrosinase expression. Finally, melanin from P. penguin, the final production of Mitf-Tyr-melanin pathway, was confirmed to have direct antibacterial activity. The results collectively demonstrated that PpMitf played a key role in innate immunity through activating tyrosinase-mediated melanin synthesis in P. penguin.